Drawing and ideation process in design education: A systematic literature review - Dimas Rifqi Novica; Elizabeth Wianto; Susana Andrade Campos (Cogent Arts & Humanities, 2023)
This paper reports a systematic literature review focusing on design student drawing practices using PRISMA guidelines. The review aimed at investigating the role of drawing as an ideation method in design education. We investigated papers within ten years, which were selected from five electronic databases. In total, 16 papers were included in our in-depth review. Our main findings include the identification of common themes on drawing and ideation processes in design education: design learning, design cognition, and design process; the existence of two different types of design tasks employed in design education; and a commonality of methods in design research involving drawing, such as experiment, protocol analysis, and case study. Two challenges for further research are identified: 1) Given the majority of the studies in the sample focused on final-year students as participants, it would be beneficial to see more studies involving lower-year students whom less experienced, and 2) It would be interesting to see whether transitioning back from digitally supported drawing to analogue drawing would strengthen student’s fundamentals. Overall, the systematic literature review provides a comprehensive map of research areas that will be useful for further research.